2018
DOI: 10.1016/j.cotox.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in ROS and autophagic signaling

Abstract: Reactive oxygen species (ROS) are important signaling molecules that mediate oxidative stress and cellular damage when improperly regulated. ROS and oxidative stress can activate autophagy, which generally serves as a cytoprotective negative feedback mechanism to selectively eliminate sources of ROS, including mitochondria and peroxisomes. In this review we describe the mechanisms by which ROS directly and indirectly activate autophagy, and conversely, how selective autophagy suppresses the formation of ROS. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 67 publications
0
36
0
1
Order By: Relevance
“…Here, we showed that S. pn - secreted H 2 O 2 alone was able to induce mitochondrial oxidative damage, impairing mtDNA replication and decreasing mtDNA content in lung cells. Moreover, H 2 O 2 is a type of reactive oxygen species (ROS), and as such, is an important signaling molecule that mediates oxidative stress and cellular damage (Wible and Bratton, 2018). Previous studies on intestinal health have revealed that H 2 O 2 upregulated intracellular and mitochondrial ROS expression (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that S. pn - secreted H 2 O 2 alone was able to induce mitochondrial oxidative damage, impairing mtDNA replication and decreasing mtDNA content in lung cells. Moreover, H 2 O 2 is a type of reactive oxygen species (ROS), and as such, is an important signaling molecule that mediates oxidative stress and cellular damage (Wible and Bratton, 2018). Previous studies on intestinal health have revealed that H 2 O 2 upregulated intracellular and mitochondrial ROS expression (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Which was then followed by nucleation, autophagic body formation, and fused with the lysosome, and then mitophagy was completed. Abnormal mitochondria were removed timely, and cell survival was promoted [13] . Another mechanism that has been researched at present is the HIF-1α/BNIP3 / BNIP3L pathway, the increase of ROS promotes the expression of HIF-1α and HIF-1α activates the autophagy signal of downstream BNIP3/BNIP3L gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Rhes will eliminate damaged mitochondria via mitophagy, further enhancing the mitochondrial biogenesis process. However, the continued exposure to 3-NP damages the newly born mitochondria, generating more ROS and neuronal death [43]. Hence, excessive mitophagy might promote ROS generation because Rhes works in a positive feedback loop in which it promotes mitophagy as well as produces ROS due to the damage of residual and newly formed mitochondria by 3-NP.…”
Section: Excessive Mitophagy and Mitochondrial Biogenesismentioning
confidence: 99%